2014
DOI: 10.1039/c4dt00181h
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photocatalytic CO2-reduction activity of electrospun mesoporous TiO2 nanofibers by solvothermal treatment

Abstract: Photocatalytic reduction of CO2 into renewable hydrocarbon fuels using semiconductor photocatalysts is considered as a potential solution to the energy deficiency and greenhouse effect. In this work, mesoporous TiO2 nanofibers with high specific surface areas and abundant surface hydroxyl groups are prepared using an electrospinning strategy combined with a subsequent calcination process, followed by a solvothermal treatment. The solvothermally treated mesoporous TiO2 nanofibers exhibit excellent photocatalyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 46 publications
(42 reference statements)
1
71
1
Order By: Relevance
“…This concludes that the defect concentration with Ti 3 þ is extremely low. The difference of 5.79 eV between the peaks indicates the presence of titanium in its tetravalent state [23,24]. The binding energy of Ti core levels remained constant up to the thermal treatment at 800°C, and shifted to lower energy side of $ 467.8 and 457.8 eV respectively, at a higher temperature (1000°C).…”
Section: Structural Characterizationmentioning
confidence: 83%
“…This concludes that the defect concentration with Ti 3 þ is extremely low. The difference of 5.79 eV between the peaks indicates the presence of titanium in its tetravalent state [23,24]. The binding energy of Ti core levels remained constant up to the thermal treatment at 800°C, and shifted to lower energy side of $ 467.8 and 457.8 eV respectively, at a higher temperature (1000°C).…”
Section: Structural Characterizationmentioning
confidence: 83%
“…Yu and co-workers have prepared mesoporous TiO 2 nanofibers with high specific surface areas and abundant surface hydroxyl groups by using an electrospinning strategy combined with a subsequent calcination process, followed by a solvothermal treatment [98]. The solvothermally treated mesoporous TiO 2 nanofibers exhibit excellent photocatalytic performance on CO 2 reduction into hydrocarbon fuels, where the optimized 2-h solvothermal treatment sample shows 6-and 25-fold higher CH 4 production rate than those of TiO 2 nanofibers without solvothermal treatment and P25, respectively, due to the enhanced CO 2 adsorption capacity and the improved charge separation after solvothermal treatment.…”
Section: Mesoporous Structuralizationmentioning
confidence: 99%
“…TiO 2 nanotubes [63,97,[186][187][188][189][190][191], nanofibers [192] and nanorods [168,169,193] exhibited a much better photocatalytic activity for CO 2 reduction than P25 or TiO 2 NPs. For instance, Fu et al [192] demonstrated that the TiO 2 nanofibers with a 2-h solvothermal treatment exhibited the highest activity for photocatalytic reduction of CO 2 to CH 4 , which was about 6 and 25 times higher than those of TiO 2 nanofibers without solvothermal treatment and P25, respectively, due to the enhanced CO 2 adsorption capacity and the improved charge separation. Moreover, NaNbO 3 nanowires [194], Zn 2 GeO 4 nanoribbons [195] and nanorods [196] synthesized using a hydrothermal/solvothermal route showed much better photocatalytic activity for the conversion of CO 2 to CO or CH 4 than the corresponding samples prepared by a high-temperature solid state reaction.…”
Section: Nanostructured Photocatalystsmentioning
confidence: 99%